2013
DOI: 10.1128/jvi.02879-12
|View full text |Cite
|
Sign up to set email alerts
|

Early Adaptive Immune Responses in the Respiratory Tract of Foot-and-Mouth Disease Virus-Infected Cattle

Abstract: Foot-and-mouth disease (FMD) is a highly contagious viral disease which affects both domestic and wild biungulate species. This acute disease, caused by the FMD virus (FMDV), usually includes an active replication phase in the respiratory tract for up to 72 h postinfection, followed by hematogenous dissemination and vesicular lesions at oral and foot epithelia. The role of the early local adaptive immunity of the host in the outcome of the infection is not well understood. Here we report the kinetics of appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
44
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 37 publications
2
44
0
1
Order By: Relevance
“…This is in keeping with the findings of Pega et al who have previously shown that the FMDVspecific ASC response to live-virus challenge is largely restricted to the local lymphoid tissues draining the infection site, where FMDV undergoes proliferation (10). These data also indicate that the ASCs generated after FMDV vaccination are likely to be short-lived extrafollicular plasma cells which remain at the site of induction (11), as shown by the lack of FMDV-specific ASCs detected in the circulation systems of these animals 3 days prior to removal of the prescapular lymph node.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This is in keeping with the findings of Pega et al who have previously shown that the FMDVspecific ASC response to live-virus challenge is largely restricted to the local lymphoid tissues draining the infection site, where FMDV undergoes proliferation (10). These data also indicate that the ASCs generated after FMDV vaccination are likely to be short-lived extrafollicular plasma cells which remain at the site of induction (11), as shown by the lack of FMDV-specific ASCs detected in the circulation systems of these animals 3 days prior to removal of the prescapular lymph node.…”
Section: Discussionsupporting
confidence: 78%
“…The FMDV-specific ELISpot assay was performed using freshly isolated PBMCs. The methodology for the FMDV-specific ELISpot assay was adapted from that of Pega et al (10). Briefly, MultiScreenHA plates (Millipore, Watford, United Kingdom) were coated with 2.2 g/well of inactivated purified FMDV antigens (FMDV A22/Iraq, FMDV Asia1/Shamir, FMDV SAT1 ZIM 22/89, FMDV O TUR/5/2009, and FMDV C1/Obb/ 73/Tüb; MSD Animal Health) diluted in 0.1 M carbonate buffer (pH 9.6) for 2 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…We incorrectly anticipated that high neutralizing antibody titers at these time points would hinder recovery (49). Similarly, FMDV has successfully been isolated from lymphoid tissues from carrier sheep and cattle (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…Virulent FMDV strain O1/Campos/Brazil/58 (O1 Campos) was provided by the OIE FMD Reference Laboratory at SENASA, Argentina. Experimental infections through the oronasal route were performed with a jet nebulizer attached to an aerosol delivery system (10 7 50% tissue culture infective doses [TCID 50 ] in a 2-ml volume per animal) as previously reported (20,22). After infection, animals were monitored daily for clinical signs of FMD.…”
Section: Methodsmentioning
confidence: 99%
“…Following our previous study on the induction of local adaptive responses in naive bovines infected through the oronasal route (20), here we analyzed the local antibody production induced after systemic FMD vaccination and the responses triggered in these animals after oronasal challenge with virulent FMDV. Our results demonstrate that soon after systemic immunization with high-payload FMD vaccines, it is possible to detect virusspecific antibody-secreting cells (ASC) in lymphoid tissues distal from the inoculation spot.…”
mentioning
confidence: 99%